PASTORAL CARE AND MENTAL HEALTH LITERACY. A CASE STUDY OF PASTORS' PSYCHOLOGICAL DISTURBANCE MANAGEMENT IN REDEEMED CHRISTIAN CHURCH OF GOD, OGUN STATE, NIGERIA. - DARE ELIJAH AJAYI (International Studies Journal)
Pastoral care serves as a vital framework for addressing mental health literacy among religious leaders, particularly in managing psychological disturbances within faith communities. This study explores the intersection of pastoral care and mental health literacy, with a focus on the psychological distress experienced by Pastors in the Redeemed Christian Church of God (RCCG), Ogun State, Nigeria. Employing a descriptive method with a qualitative case study approach, the research examines the prevalence of psychological disturbances among pastors, their coping mechanisms, and the effectiveness of structured mental health literacy programs in enhancing their well-being. Findings reveal that while pastors function as primary sources of emotional and spiritual support for congregants, they often lack adequate mental health literacy, leading to difficulties in managing their psychological challenges. The study stressed the impact of targeted training interventions on improving mental health awareness, reducing stigma, and fostering a supportive environment for pastoral leaders. It also highlights the role of faith-based institutions in integrating mental health education into pastoral training curricula and establishing peer support networks to enhance psychological resilience among religious leaders. The research contributes to the growing discourse on mental health literacy within religious settings, advocating for a holistic approach that combines theological insights with psychological expertise. Recommendations include the development of structured ministry-based training in mental health literacy programs tailored to the unique needs of Pastors, with the establishment of collaborative partnerships between religious institutions and mental health professionals.